Development of an in situ CAR-T cell protocol through optical and PSMA-targeted PET imaging - Nisi Zhang; Jai Woong Seo; Elise Robinson; Angelie Rivera-Rodriguez; James Wang; Yutong Guo; Debra K. Czerwinski; Ha Rin Kim; Spencer K. Tumbale; Marina N. Raie; Basit L. Jan; Gokce Engudar; et al. (Proceedings of the National Academy of Sciences, 2025)
In situ T cell transfection methods overcome the complexity and high costs associated with conventional chimeric antigen receptor (CAR)-T therapy. However, the in situ CAR-T cell approach operates within the patient’s complex immune environment and bypasses preinfusion ex vivo cellular quality controls, necessitating advanced imaging techniques to track immune cell migration and function. Positron emission tomography (PET) can detect biochemical processes in patients and, when combined with a radiotracer specific for the engineered cells, can monitor CAR-T cell trafficking. Herein, we develop an approach for in situ T cell generation, tracking, and functional assessment using anti-CD5-conjugated lipid nanoparticles for codelivering CD19 CAR mRNA (mCAR19) and a prostate-specific membrane antigen mRNA (mPSMA) tag. With interleukin-7 (IL-7) preconditioning and repeated administration, this approach achieves tumor-free survival in 75% of B cell lymphoma-bearing mice (similar efficacy to ex vivo approaches), and through PET imaging of 68 Ga-PSMA-617, the generation and tumor infiltration of in situ-engineered PSMA-tagged CD19 CAR-T cells is validated.